2021
DOI: 10.3390/plants11010099
|View full text |Cite
|
Sign up to set email alerts
|

Hop Leaves as an Alternative Source of Health-Active Compounds: Effect of Genotype and Drying Conditions

Abstract: In hop cultivation, one-third of the crop is a valuable product (hop cones), and two-thirds is unexploited biomass, consisting mainly of leaves and stems, which, in a circular economy approach, can be recovered and, once stabilized, supplied to industrial sectors, such as cosmetics, pharmaceuticals and phytotherapy, with high added value. In this regard, this study aimed to investigate the effects of two different drying methods: oven drying (OD) at 45 °C and freeze-drying (FD), on the overall nutraceutical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…It has been shown that several active molecules detected in hop may be considered for their antioxidant and/or antimicrobial activities. Among these compounds, prenylated polyphenols were shown to have many biological activities that might be useful for human health [ 27 , 28 , 31 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that several active molecules detected in hop may be considered for their antioxidant and/or antimicrobial activities. Among these compounds, prenylated polyphenols were shown to have many biological activities that might be useful for human health [ 27 , 28 , 31 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hop plants ( Humulus lupulus L.) are cultivated for the brewing industry, where only female cones are considered valuable products due to the presence of bitter acids [ 27 ]. In the end, two-thirds of the plant (mainly leaves and stems) is unexploited, whereas the whole plant is known to contain a wide range of active biomolecules, such as anti-inflammatory compounds [ 28 , 29 ]. The valorization of other hop plant parts, such as leaves, might represent a real opportunity to improve OA [ 28 , 30 ], since hop compounds have already shown their efficacy in reducing inflammation in other pathologies [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They take into account the studies regarding the antioxidant effects of hops’ components, correlated with the consumer’s desire to have products of natural origin. Moreover, in addition to hops fruits, the use of hops leaves with a high antioxidants content is also considered [ 85 ]. Of course, most of the new products benefit not only from the antioxidant effect, but also from other positive actions of the existing substances in hops, with convergent effects.…”
Section: Safety and Prospectsmentioning
confidence: 99%
“…Regarding the polyphenolic component, in recent years, studies have shown the effectiveness of using hop extracts against some chronic-degenerative diseases, such as cancer and metabolic syndrome [9]. This perspective has prompted some researchers to investigate the use of agricultural waste from the hop harvest as a source of secondary metabolites for use in industries other than brewing, such as food, cosmetics, and pharmaceuticals [10]. Hop is a very widespread species in the wild state in Central and Northern Italy, but its cultivation is not strongly developed.…”
Section: Introductionmentioning
confidence: 99%